Travail textuel et compétence textuelle dans l’enseignement d’une L2 à de jeunes apprenant-e-s - Ingo Thonhauser (Babylonia)
In this project I focus on the way texts are used in teaching German as a Foreign Language at primary school level. I analyse the genres present in the regional curriculum (the Plan d’études Romand) and in two of the textbooks in use. Interviews with teachers in a primary school in the canton of Vaud in Western Switzerland and observation of classroom practice show that authentic texts undergo a significant transformation in the context of language teaching with far-reaching implications. Authentic, “real life” texts (and genres) take on the characteristics of material for teaching and learning. Teachers need specific competences in order to provide learning opportunities based on the use of texts and learners need to develop specific literacies in order to take advantage of these opportunities.